A meta-analysis of the association between mindfulness and motivation - Li, Li-ying; Meng, Xue; Hu, Wen-ting; Geng, Jia-sen; Cheng, Tian-hua; Luo, Jia-cheng; Hu, Ming-yu; Li, Hai-yue; Wang, Yi; Wang, Yan-yu (Frontiers in Public Health, 2023)
Introduction: Mindfulness reflects attention to the present moment in a non-judgmental way and has been linked to individual autonomy and motivation, but conclusions are inconsistent. The purpose of this review was to summarize previous studies to explore the relationship between mindfulness and motivation and its intervention effects. Methods: Literature searches were conducted in five electronic databases. Both correlational studies assessing the association between motivation and mindfulness and experimental studies to verify the effect of intervention were included. Results: Six papers with seven intervention studies and twenty-three papers with twenty-seven correlational studies met the inclusion criteria. Meta-analysis showed that mindfulness was positively correlated with intrinsic motivation (r = 0.28, p < 0.0001) and total motivation (r = 0.37, p < 0.0001) but had no significant correlation with extrinsic motivation (r = 0.01, p = 0.93) or amotivation (r = -0.17, p = 0.14). Effect-size estimates suggested that mindfulness intervention was beneficial to motivation promotion, but the effect was at a low level (g = 0.12). Conclusion: We found consistent support for mindfulness practice relating to motivation promotion, especially on intrinsic motivation development. However, there was still a portion of heterogeneity that could not be explained and needed to be identified in future studies.